Indications for renal transplantation in children: What a pediatrician should know ? - A V Lalitha; Swathi Rao; Nivedita Kamath (Wolters Kluwer Medknow Publications, 2018)
Renal transplantation is the best modality of treatment for end stage renal disease in children when compared to chronic dialysis. The growth, development and quality of life in these children are significantly better after transplantation. There has been a marked increase in the number of children undergoing renal transplantation in the recent years. The short term graft survival rates have increased with improved immunosuppression, but the long term outcome is still poor due to chronic graft rejection and opportunistic infections. In developing countries renal transplantation is not accessible to many children due to economic issues, lack of expertise and the absence of a strong deceased donor program. This article is a brief review of the indications and other aspects of pre-operative evaluation of pediatric renal transplant recipients.